2021
DOI: 10.1002/gps.5509
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with subjective cognitive decline in dementia‐free older adults—A population‐based study

Abstract: Background Subjective cognitive decline (SCD) is common in older adults, affects quality of life (QoL), and may represent the earliest clinical manifestation of cognitive decline evolving to dementia. Still little is known about factors associated with SCD. Objectives (1) Assess the associations between SCD and demographic, social, clinical, and personality characteristics as well as QoL, with and without adjustment for objective cognitive performance, and (2) investigate the relations between neuroticism, QoL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
(60 reference statements)
0
22
1
Order By: Relevance
“…A recent large epidemiological community-based study from Norway reported that 35% of adults older than 70 years had a diagnosis of MCI, and a Swiss community-based study reported a prevalence of 18.5%. In addition, a review reported a prevalence of 23.8% for the diagnosis of subjective cognitive decline [42, 49, 50]. We suggest that raised awareness about memory problems as a possible first sign of dementia and insight into their own decline of memory function by increasing age could explain the high proportion of complainers of both sexes.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…A recent large epidemiological community-based study from Norway reported that 35% of adults older than 70 years had a diagnosis of MCI, and a Swiss community-based study reported a prevalence of 18.5%. In addition, a review reported a prevalence of 23.8% for the diagnosis of subjective cognitive decline [42, 49, 50]. We suggest that raised awareness about memory problems as a possible first sign of dementia and insight into their own decline of memory function by increasing age could explain the high proportion of complainers of both sexes.…”
Section: Discussionmentioning
confidence: 83%
“…The association between memory complaints and significant cognitive impairment and dementia has been examined in numerous studies, but only some studies have compared self-reported cognitive complaints (SCC) with scores on the MMSE and MoCA among home-dwelling older people [34-42]. All these studies indicate that older adults with SCC are at higher risk of developing dementia than those with no complaints, although a systematic review concludes that one should not use SCC as a predictor of future development of dementia [35].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, little is known about the role played by other psychological factors in predicting the occurrence of subjective cognitive complaints. Concerning this issue, recently, Zullo et al ( 2021 ) argued that cognitive complaints in older individuals are predicted by higher neuroticism and depressive symptoms and are associated with lower extraversion and worse categorical verbal fluency skills. A related research trend showed that global psychological well-being in healthy aging was predicted by self-reported depressive symptoms and two metacognitive measures, including CFQ score (Fastame et al 2014a ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the current study intended to investigate the following: (1) the nature of the relationships between the CFQ (Broadbent et al 1982 ) scores and several self-reported psychological well-being measures (i.e., including optimism) and objectively assessed executive functions, respectively; (2) whether older individuals reporting higher CFQ (Broadbent et al 1982 ) scores also reported lower mental health indices and showed worse measures of executive functioning. Overall, following Zullo et al ( 2021 ), the current study intended to provide a better understanding of the link between several psychological factors (i.e., the efficiency of executive functions and mental health) and a well-known self-reported metacognitive functioning measure that assesses perception, motor, and memory errors in everyday life, namely the CFQ (Broadbent et al 1982 ). That is, by embracing an applied perspective, the emerging evidence could provide useful information for the implementation of preventive and empowering interventions aimed at improving the quality of life in the last decades of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation